Building climate-resilient food systems for Pacific Islands - Bell, J.; Taylor M (2015)
The 22 Pacific Island countries and territories face many challenges in building the three main pillars of food security: availability, access and appropriate use of nutritious food. These challenges arise because many Pacific Island countries and territories are undergoing rapid population growth and urbanization; communities cannot engage in broad-acre agriculture and livestock grazing due to shortages of arable land; opportunities to earn income are limited; and cheap, low-quality food imports are readily available due to burgeoning global trade. As a result, many Pacific Island countries and territories are now highly dependent on imported food, and the incidence of noncommunicable diseases is among the highest in the world — 9 of the 10 countries with the highest rates of overweight and obesity and 7 of the 10 countries with the highest rates of diabetes are Pacific Island nations.